2022
DOI: 10.1007/s00445-022-01576-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the topography of stratovolcanoes on the propagation and channelization of dense pyroclastic density currents analyzed through numerical simulations

Abstract: We applied systematically the branching energy cone model to a large (𝑁 = 50) set of stratovolcanoes around the world in order to evaluate the main topographic characteristics that may control the propagation of dense pyroclastic density currents (PDCs). Results indicate that channelization efficiency of a PDC is strongly controlled by the relative scale between flow size and volcano topographic features. Most of the studied stratovolcanoes topographies are able to induce significant PDC channelization in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This general effect is compounded by processes like PDC channelization and overbanking, which also depend on flow size and mobility, and topography surrounding the vent location. All this is compatible with previous observations made at several volcanoes worldwide (e.g., Aravena & Roche, 2022; Breard et al., 2023; Charbonnier et al., 2020; Charbonnier & Gertisser, 2012; Gueugneau et al., 2020; Ogburn & Calder, 2017; Ogburn et al., 2014; Tennant et al., 2021; Tierz et al., 2018). Notwithstanding, it is also important to place the PDC modeling developed using TITAN2D into the wider context of what is currently known in terms of PDC dynamics.…”
Section: Discussionsupporting
confidence: 92%
“…This general effect is compounded by processes like PDC channelization and overbanking, which also depend on flow size and mobility, and topography surrounding the vent location. All this is compatible with previous observations made at several volcanoes worldwide (e.g., Aravena & Roche, 2022; Breard et al., 2023; Charbonnier et al., 2020; Charbonnier & Gertisser, 2012; Gueugneau et al., 2020; Ogburn & Calder, 2017; Ogburn et al., 2014; Tennant et al., 2021; Tierz et al., 2018). Notwithstanding, it is also important to place the PDC modeling developed using TITAN2D into the wider context of what is currently known in terms of PDC dynamics.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that, in addition to the significant difference in the collapsing volumes of ES2 and ES3, the strong differences in the resulting hazard maps are also modulated by a change in the behavior of the simulated PDCs above a threshold of collapsing volume of pyroclasts, which in fact coincides with the transition between the calibrated volumes of pyroclasts of ES2 and ES3. The capacity of the topography of stratovolcanoes to influence the behaviour of PDCs has been recently addressed by Aravena and Roche (2022), who classified Tungurahua volcano as a case of intense proximal channelization and moderate distal channelization based on the analysis of numerical simulations of dense PDCs. This is due to the well-defined radial ravines that favor PDC propagation in proximal domains and pronounced tangential valleys (Puela, Chambo and Pastaza rivers) that buffer the increase of runout distance toward N, NW and NE and of inundation area when PDCs reach the edifice base (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This makes even more critical the need to refine our knowledge about large-scale explosive events at Tungurahua volcano. In addition, Aravena and Roche (2022) recognized the clear effect of proximal obstacles in PDC propagation at Tungurahua, which is probably due to the crater topography and the presence of the ~3 ka BP collapse scar that limit the propagation of small-scale PDCs towards NE. Although probabilistic volcanic hazard maps as those presented here integrate a large amount of information that are more or less easily understandable by the vast majority of the volcanological community, they are not directly accessible by local communities and decision makers (see for example Thompson et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit remarkably long flow runouts compared to other geophysical granular flows of similar volume (Dade and Huppert 1998;Druitt, 1998;Calder et al 1999;Iverson and Vallance 2001). Previous studies on CPCs have demonstrated that channelization can enhance flow runout by confining the entire mass into a restricted area, preventing rapid lateral spreading and efficient energy dissipation (Woods et al 1998;Calder et al 1999;Andrews and Manga 2012;Jessop et al 2012;Charbonnier et al 2013;Ogburn et al 2014;Aravena and Roche 2022). Furthermore, a high interstitial gas pore pressure and related fluidization in the concentrated basal layer has been proposed as an efficient mechanism to reduce the inter-particle friction and also enhance flow runout (Sparks 1978;Wilson 1980;Druitt et al 2004;Bareschino et al 2007;Dufek 2016;Lube et al 2020), as demonstrated by numerous experimental works (Druitt et al 2007;Girolami et al, 2015;Roche et al 2010;Rowley et al 2014;Smith et al 2018Smith et al , 2020 and numerical studies (Gueugneau et al 2017;Breard et al 2019Breard et al , 2022Lube et al 2019;Aravena et al 2021).…”
Section: Concentrated Pyroclastic Currentsmentioning
confidence: 99%